Un libro de secretos : hijas ilegítimas, padres ausentes - Holroyd, Michael (Ojo del tiempo, 2015)
The author shares the stories of unknown women who played significant roles in the lives of prominent figures, including a mistress shared by the second Lord Grimthorpe and the Prince of Wales (Alice Keppel), a creative muse of Auguste Rodin (Eve Fairfax), and a novelist lover of Vita Sackville-West (Violet Trefusis). He also reflects on himself as investigator and biographer.